Spatial Mapping of Soil Moisture in an Agricultural Farm through Geostatistical Approach - Debashis Chakraborty (Journal of the Indian Society of Soil Science, 2022)
Spatiotemporal changes in near-surface soil moisture (NSSM; 0-5 cm) were captured over the research farm (242 ha) at ICAR-Indian Agricultural Research Institute, New Delhi during rabi (winter) season by applying geostatistical techniques. Ranges of NSSM have been different on different days, and was not related to either bulk density or clay content of the surface layer. Even the best-fitting semi-variogram models were different with an average root mean square error of 6.8 over the study period. The minimum separation distance between two sampling points was ~6 m, and nearly 50% variability could be explained by the nugget indicating small scale variations of soil moisture. Spatial variability maps of NSSM were prepared using ordinary kriging wherein a few distinct wetness zones were apparent. Sub-surface soil moisture (SSSM) was correlated with NSSM till 40 cm depth, making plausibility of root-zone soil moisture mapping from surface measurements. The kriged maps will help in scheduling irrigation and deciding sowing dates over a large farm with limited number of in-situ point observations.